Effectuating Change: A Tool Box of Strategies for Reducing the Unnecessary Use of Administrative Court Orders - Runyon, Sarah (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2020)
This article is a sequel to Correctional Afterthought, in which the author argued that Gladue’s promise of reducing Indigenous over-incarceration by employing non-custodial measures has been thwarted. By insisting on alternatives to incarceration, the justice system is forced to rely on administrative court orders managed by provincial probation services. The judiciary and justice system participants possess a misplaced faith in the probationary regime, which functions as a repressive system of control that necessarily views the Indigenous accused as a risk that must be managed. The most common probation conditions, far from fostering reintegration, serve to erode individual autonomy, engender mistrust, alienation, resentment, and resistance; in the end creating disunity and discord.  The aim of Effectuating Change is to offer a sound proposal for legislative reform and in the interim, practical sentencing solutions to deliver the true intention of Gladue and its offspring. Regardless of whether the proposals in this article are vigorously critiqued, supported, denounced or modified the hope is that they create a springboard for creative solutions to the problems identified in Correctional Afterthought.